Natural Language Processing for Automated Radiology Report Generation: A Paradigm Shift in Clinical Workflow - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The exponential growth in medical imaging studies burdens radiologists, as traditional manual reporting causes inter-observer variability and workflow bottle...
Keywords: Diagnostics; Artificial Intelligence; Patient Care; Machine Learning; Clinical Decision Support